Pressure Overload Greatly Promotes Neonatal Right Ventricular Cardiomyocyte Proliferation: A New Model for the Study of Heart Regeneration. Issue 11 (2nd June 2020) - Ye, Lincai; Wang, Shoubao; Xiao, Yingying; Jiang, Chuan; Huang, Yanhui; Chen, Huiwen; Zhang, Haibo; Zhang, Hao; Liu, Jinfen; Xu, Zhuoming; Hong, Haifa
Abstract : Background: Current mammalian models for heart regeneration research are limited to neonatal apex amputation and myocardial infarction, both of which are controversial. RNAseq has demonstrated a very limited set of differentially expressed genes between sham and operated hearts in myocardial infarction models. Here, we investigated in rats whether pressure overload in the right ventricle, a common phenomenon in children with congenital heart disease, could be used as a better animal model for heart regeneration studies when considering cardiomyocyte proliferation as the most important index. Methods and Results: In the rat model, pressure overload was induced by pulmonary artery banding on postnatal day 1 and confirmed by echocardiography and hemodynamic measurements at postnatal day 7. RNA sequencing analyses of purified right ventricular cardiomyocytes at postnatal day 7 from pulmonary artery banding and sham‐operated rats revealed that there were 5469 differentially expressed genes between these 2 groups. Gene ontology and Kyoto Encyclopedia of Genes and Genomes analysis showed that these genes mainly mediated mitosis and cell division. Cell proliferation assays indicated a continuous overproliferation of cardiomyocytes in the right ventricle after pulmonary artery banding, in particular for the first 3 postnatal days. We also validated the model using samples from overloaded right ventricles of human patients. There was an approximately 2‐fold increase of Ki67/pHH3/aurora B‐positive cardiomyocytes in human‐overloaded right ventricles compared with nonoverloaded right ventricles. Other features of this animal model included cardiomyocyte hypotrophy with no fibrosis. Conclusions: Pressure overload profoundly promotes cardiomyocyte proliferation in the neonatal stage in both rats and human beings. This activates a regeneration‐specific gene program and may offer an alternative animal model for heart regeneration research.